A portable bioimpedance instrument for monitoring residual limb fluid volume in people with transtibial limb loss: A technical note. (June 2019) - Hinrichs, Paul; Cagle, John C.; Sanders, Joan E.
Abstract : Portable system applied 26 frequency bursts per second between 3 kHz and 1 MHz. Unit was of dimension 15 cm × 11 cm × 4 cm, weighed 3.9 N, and sampled at 30 Hz. Mean RMS errors were 0.07% for Re, 2.23% for Ri, and 1.15% for Cm . Errors at high frequencies were from the voltage controlled current source. Abstract: People with transtibial limb loss experience daily changes in volume of their residual limb that affect the fit of their prosthetic socket. A portable instrument was developed to monitor fluid volume changes outside of the laboratory setting. The bioimpedance system applied 26 current bursts per second at frequencies between 3 kHz and 1 MHz, and sensed voltage at up to six channels. Among six voltage-controlled current source circuits and five receive-channel amplifier topologies considered, a differential Howland current pump and a single receive-channel instrumentation amplifier proved the best combination of low noise and low power consumption. Mean RMS errors were 0.07% for extracellular fluid resistance, 2.23% for intracellular fluid resistance, and 1.15% for membrane capacitance.